Motivasi belajar, pemicu respon mahasiswa dalam menggapai prestasi - Firda Widya Safinah; Mukhamad Zaenal Arifin; Ryan Mahardika Alif Rosyidi; Zunaida Erma Rahmawati (UIN Maulana Malik Ibrahim Malang, 2023)
Learning motivation influences the emergence of triggers to achieve academic excellence. This article explains that learning motivation can generate student responses toward academic achievement. This research adopts the grounded research method. The participants in the study were four students. Data analysis employs four constructivist steps: verbatim from interview transcripts, data condensation, categorization, and sub-theme conclusion. The findings of this research indicate that, first, the identified forms of learning achievement include having an outrageous sense of responsibility, being willing to take risks, and not being afraid of failure. Second, self-development can shape these achievements, including self-confidence and exploring one's potential. Third, learning motivation drives various aspects, such as failure reflection and reinforcement. Thus, individuals can minimize and overcome possible barriers with encouragement to motivate themselves, leading to academic excellence.KEY WORDS: learning motivation; achievement; self-introspection; self-developmentABSTRAKMotivasi belajar mempengaruhi munculnya pemicu untuk mencapai prestasi akademik. Artikel ini menjelaskan bahwa motivasi belajar dapat menghasilkan respon siswa terhadap prestasi akademik. Penelitian ini menggunakan metode grounded research. Partisipan dalam penelitian ini adalah empat mahasiswa. Analisis data menggunakan empat langkah konstruktivis: kata demi kata dari transkrip wawancara, kondensasi data, kategorisasi, dan kesimpulan sub-tema. Temuan penelitian ini menunjukkan bahwa, pertama, bentuk-bentuk prestasi belajar yang teridentifikasi termasuk memiliki rasa tanggung jawab yang tinggi, bersedia mengambil risiko, dan tidak takut gagal. Kedua, pengembangan diri dapat membentuk prestasi tersebut, termasuk rasa percaya diri dan menggali potensi diri. Ketiga, motivasi belajar mendorong berbagai aspek, seperti refleksi kegagalan dan penguatan. Dengan demikian, individu dapat meminimalkan dan mengatasi hambatan yang mungkin terjadi dengan dorongan untuk memotivasi diri mereka sendiri, yang mengarah pada keunggulan akademik.Top of FormBottom of FormKATA KUNCImotivasi belajar; prestasi; introspeksi diri; pengembangan diri Copyright ©2023. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: CreativeCommons — Attribution-NonCommercial-ShareAlike 4.0 International — CCBY-NC-SA 4.0